Hierarchical structure of nanoporosity of Mexican natural zeolites of clinoptilolite type - Gabriela Itzel-Hernandez; Miguel Angel Hern; Roberto Portillo; Vitalii Pavlovich Petranovskii; Aleksey Nikolaevich Pestryakov; Efrain Rubio (Известия Томского политехнического университета: Инжиниринг георесурсов, 2018)
The relevance of the research is caused by the large number of newly discovered zeolite fields in Mexico. For practical use of these materials, the appropriate characteristics are required, in which experimental models are proposed that provide reliable and usable data for each of the declared deposits. The main aim of this research work is to evaluate the adsorption capacity of natural clinoptilolite zeolites from different deposits in Mexico to assess their nanoporosity and to evaluate whether they have some mesoporous voids. Objects of the researchare zeolite tuffs from seven different deposits located in Mexico. These deposits are poorly studied and characterized by a complex mineral composition of rocks. Methods. Zeolites were studied by XRD, Scanning Electron Microscopy, energy dispersive spectroscopy, thermogravimetric methods and Differential scanning calorimetry. All samples were also studied by N 2 adsorption method. The surface areas of BET, Langmuir, and t-plots of all the investigated zeolites were estimated. The total pore volume was estimated in accordance with the Gurvitsch rule. The microporosity of these natural zeolites was measured using the DA high-resolution adsorption method. Information on the distribution of micropore sizes was obtained from the data of the isothermal adsorption-desorption. Research results. The nanoporosity of natural clinoptilolite zeolites from new deposits is estimated using traditional experimental methods such as DRX, SEM, EDS and HRADS of N 2 at the boiling point of liquid nitrogen. The latter method evaluates texture parameters, in which micropores are estimated by t-graphs. The nanopore distribution is determined using the recently proposed approximation, called differential adsorption curves. Studies of TGA and DSC show the presence of three types of adsorbed water: adsorbed water in macropores, water adsorbed in the outer region of zeolite (mesopores) and water adsorbed in micropores. This behavior was confirmed by N 2 adsorption: microporous filling, multilayered formation on the outer surface of zeolite tuff, and the phenomenon of capillary condensation arising in macropores.